The Pitfalls of Neglecting the Integration of Young Women in Business: The Case of the Democratic Republic of Congo - Lipoko, Darla Urmiche Diya; Iwu, Chux Gervase; Opute, Abdullah Promise; Kappo-Abidemi, Christiana Omolayo (Reshaping Sustainable Development Goals Implementation in the World: Proceeding of 7th International Conference on Business and Management Dynamics, 2021)
Given the patriarchal nature of the African society, females are often secondary. In patriarchal societies, men are viewed as forebearers of knowledge and hence dominate other considerations. A direct consequence therefore is structural discrimination of women, and small businesses are owned and managed by men. Youth unemployment is notably high in the Democratic Republic of the Congo, and especially among females. Notably too, one critical factor that drives entrepreneurship start-ups is self-employment often induced by unemployment. In patriarchal societies, not only are there few opportunities for women but also women face more constraints than their male counterparts. Inspired by the gap in the literature, this study utilizes the descriptive literature review approach to understand the problems faced by young women when starting a business in Kinshasa, the Democratic Republic of Congo. Understanding this theoretical premise and from the perspective of the explored population is important given the criticality of entrepreneurship to economic growth (including unemployment and poverty reduction). In addition, this study would contribute to strategic policy change for achieving productive entrepreneurship. Finally, this study flags research directions for steering necessary research towards productive entrepreneurship goals.